Seasonal variations of empyema in Taiwan: A 10-year analysis - Ya-Fu Cheng; Yi-Ling Chen; Wan-Ling Chuang; Chia-Che Chang; Bing-Yen Wang (Elsevier, 2024)
Background: Empyema is a serious infection in pleural space. Finding out seasonal variations of empyema and its pathogens can help in providing preventive measures, and implicating future researches. Methods: This study is a 10-year observational study in a single center. Patients with empyema thoracis receiving thoracoscopic decortication between January 2012 and December 2021 were included in the study. Results: There were 1082 empyema patients enrolled in this study. No seasonal variation was noted (spring = 25.7 %, summer =25.5 %, autumn = 24.8 %, winter = 24.0 %). However, we observed seasonal variations in pathogens. Streptococcus species had slightly higher prevalence in winter and spring than summer and autumn (54.3 % vs. 45.7 %) without significant difference (p = 0.251). On the contrary, Staphylococcus species occurred more often in summer and autumn than winter and spring (61.5 % vs. 38.5 %) (p = 0.035). Klebsiella species were more likely found in autumn (34.9 %) (p = 0.050), and Pseudomonas species showed no peak prevalence in any season (p = 0.423). The incidence of Streptococcus species increased over the years. Conclusions: Although no seasonal variation was found in severe empyema patients requiring surgery, there were seasonal variations for the pathogens in Taiwan. The medical community should focus on Streptococcus species in winter and spring and Staphylococcus species in summer and autumn.